Current concepts in combination therapy for the treatment of hypertension: combined calcium channel blockers and RAAS inhibitors - Alberto F Rubio-Guerra; David Castro-Serna; Cesar I Elizalde Barrera; et al (Dove Medical Press, 2009)
Alberto F Rubio-Guerra1, David Castro-Serna2, Cesar I Elizalde Barrera2, Luz M Ramos-Brizuela21Metabolic and Research Clinic, 2Internal Medicine Department, Hospital General de Ticomán SS DF, MéxicoAbstract: Recent guidelines for the management of hypertension recommend target blood pressures <140/90 mmHg in hypertensive patients, or <130/80 mmHg in subjects with diabetes, chronic kidney disease, or coronary artery disease. Despite the availability and efficacy of antihypertensive drugs, most hypertensive patients do not reach the recommended treatment targets with monotherapy, making combination therapy necessary to achieve the therapeutic goal. Combination therapy with 2 or more agents is the most effective method for achieving strict blood pressure goals. Fixed-dose combination simplifies treatment, reduces costs, and improves adherence. There are many drug choices for combination therapy, but few data are available about the efficacy and safety of some specific combinations. Combination therapy of calcium antagonists and inhibitors of the renin-angiotensin-aldosterone system (RAAS) are efficacious and safe, and have been considered rational by both the JNC 7 and the 2007 European Society of Hypertension – European Society of Cardiology guidelines for the management of arterial hypertension. The aim of this review is to discuss some relevant issues about the use of combinations with calcium channel blockers and RAAS inhibitors in the treatment of hypertension.Keywords: hypertension, calcium channel blockers, renin-angiotensin-aldosterone system inhibitors, fixed-dose combination, adherence